2016
DOI: 10.1111/jvh.12508
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic expression of proteasome subunit alpha type‐6 is upregulated during viral hepatitis and putatively regulates the expression of ISG15 ubiquitin‐like modifier, a proviral host gene in hepatitis C virus infection

Abstract: The interferon-stimulated gene 15 (ISG15) plays an important role in the pathogenesis of hepatitis C virus (HCV) infection. ISG15-regulated proteins have previously been identified that putatively affect this proviral interaction. The present observational study aimed to elucidate the relation between ISG15 and these host factors during HCV infection. Transcriptomic and proteomic analyses were performed using liver samples of HCV-infected (n = 54) and uninfected (n = 10) or HBV-infected controls (n = 23). Prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
(76 reference statements)
1
7
0
Order By: Relevance
“…In contrast, our study showed that ISG15 levels were positively correlated with viral loads, implying a contradictory effect of ISG15 on antiviral activities. This is consistent with studies showing that ISG15 can promote HCV replication [ 19 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, our study showed that ISG15 levels were positively correlated with viral loads, implying a contradictory effect of ISG15 on antiviral activities. This is consistent with studies showing that ISG15 can promote HCV replication [ 19 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…ISG15 plays also a role in the response to many viral infections [9,15-18]. A recent study has shown that knockdown of ISG15 results in suppression of hepatitis C virus (HCV) replication in vitro by promoting the IFN response, suggesting involvement of ISG15 in regulating HCV replication [19,20]. Furthermore, patients who respond favorably to IFN treatment of hepatitis C have low expression levels of ISG15 and its conjugates in the liver compared to non-responders [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…14 In addition, high levels of ISG15 in the liver of patients with HCV infection were associated with an unfavourable HCV genotype 1, a high hepatic HCV load and a low antiviral response to IFN compared to patients who did not present such characteristics. 13 These findings indicate the potential of ISG15 as a biomarker of IFN treatment response in patients with HCV infection.…”
Section: Illustrative Casementioning
confidence: 77%
“…12 Furthermore, upregulated expression of ISG15 was observed at both the mRNA and protein levels in liver tissue samples from patients with HCV infection compared to the levels detected in uninfected controls. 13 Similarly, the abundance of ISG15 transcripts was found to be increased in human PBMCs and liver cells in patients with HCV infection who were unresponsive to IFN treatment compared to the levels in corresponding IFN-responsive patients. 14 In addition, high levels of ISG15 in the liver of patients with HCV infection were associated with an unfavourable HCV genotype 1, a high hepatic HCV load and a low antiviral response to IFN compared to patients who did not present such characteristics.…”
Section: Illustrative Casementioning
confidence: 91%
“…Boltjes et al (29) demonstrated that a direct interaction between HBsAg and KC resulted in HBsAg uptake, induction of cytokine production, and the induction of IFN-γ production by NK cells. Alternatively, phagocytosis of HBV itself or -infected hepatocytes by KC may allow intracellular TLR3 exposure to viral RNA (30, 31). …”
Section: Discussionmentioning
confidence: 99%